Rapid Northwestward Extension of the East Asian Summer Monsoon Since the Last Deglaciation: Evidence From the Mollusk Record - Dong, Yajie; Wu, Naiqin; Li, Fengjiang; Lu, Houyuan (Frontiers in Earth Science, 2021)
The magnitude and rate of the expansion of the East Asian summer monsoon (EASM) rain belt under future climatic warming are unclear. However, appropriate ecological proxy data may provide an improved understanding of the spatial extension of the EASM during past warming intervals. We reconstructed the spatiotemporal pattern of the extension of the EASM since the Last Glacial Maximum (LGM), using six well-dated mollusk fossil sequences from Chinese loess sections located on the modern northern edge of the EASM. The abundance of typical dominant mollusk species indicative of EASM intensity shows a delayed response, from ~17 ka in the southeastern sections to ~9 ka in the northwestern sections, during the last deglacial warming. Isoline plots based on a mollusk data synthesis show that the mollusk EASM indicators have a northeast–southwest zonal distribution for both the present-day, the cold LGM, and the warm mid-Holocene, which is consistent with the spatial pattern of modern precipitation. The resulting estimated expansion rate of EASM intensity accelerated during ~12–9 ka (~50 km/ka), which corresponds to the early Holocene interval of rapid climatic warming, a northwestward shift of ~150 km compared to today. This implies that the northern fringe of the EASM in northern China will become wetter in the coming century, under moderate warming scenarios.